Pengujian Kualitas Website Universitas Sahid Surakarta Menggunakan Metode Mc Call - Triyanto, Triyanto; Charolina, Astri (Gaung Informatika, 2011)
Websites of Sahid  university Surakarta is still  difficulty  in renewing  the availability of information because only one admin who manages  the website,  so that much of the information  or  announcements  that are not  updates.  This study aims  to develop the website of university Sahid Surakarta. This website  is an extension of  the previous  website  management  website  admin  only done  one  course,  turned into  a website that  has a lot of  admin  for ease in  its management  and  presentation of information and menus are easily understood by the user. System development using object-based method,  the website was built with the needs of the university, both visitors and admin managers. A website called qualified if it meets  several  criteria  of quality.  Software quality measurement  in this study using methods  McCall,  with  the five  factors  used  for assessing  the  efficiency,  reliability, maintainability, usability, and compability. McCall method was chosen because it has been widely used and are good enough to measure the quality of a software. Products derived from  this study is  a  university  Sahid Surakarta  website elearning  integration,  where websites  are built  with the needs of  the university. Features  presented in  this  website  include  the ease of  managing the  news  and information,  registration  of students  online  and print  out the registration form. After testing the method of McCall, the system is a total value of quality (71,75  %). Thus the results of  such testing,  the website is  expected to  facilitate  the management of  the website and the presentation of information so it can be applied to the Sahid university of Surakarta.